Design considerations of high performance optical code division multiple access: A new spectral amplitude code based on laser and light emitting diode light source - Hilal Adnan, Fadhil; Syed Alwee Aljunid, Syed Junid, Prof. Madya; R. Badlishah, Ahmad, Prof. Madya Dr. (The Institution of Engineering and Technology, 2010)
Link to publisher's homepage at http://www.ietdl.org/